Self-Medication with Antibiotics among University Students in LMIC: A systematic review and meta-analysis - Rixiang Xu; Tingyu Mu; Guan Wang; Jing Shi; Xin Wang; Xiaoli Ni (Journal of Infection in Developing Countries)
Introduction: Self-medication with antibiotics (SMA) is common among university students in low and middle-income countries (LMICs). However, there has been no meta-analysis and systematic review in the population.